Edison Beaker, creature seeker. 2, The lost city - Cammuso, Frank (Viking, 2019)
Going back through the Night Door, Edison Beaker finds himself in the bounds of a city that is drowning in darkness. He must find a way to save his friends and defeat his creature foes.